Forgotten souls : a social history of the Hong Kong cemetery - Lim, Patricia (Royal Asiatic Society Hong Kong studies series., 2011)
The book has recorded the inscriptions on all 8,000 graves in the HK Cemetery to provide a rich description of life in Hong Kong during the first 100 years approximately from its colonization and a wonderful series of anecdotes.